Population-Based Analysis of Survival for Hypoplastic Left Heart Syndrome - Hirsch, Jennifer C.; Copeland, Glenn; Donohue, Janet E.; Kirby, Russell S.; Grigorescu, Violanda; Gurney, James G. (The Journal of pediatrics, 2011)
To analyze survival patterns among infants with hypoplastic left heart syndrome (HLHS) in the State of Michigan. Cases of HLHS prevalent at live birth were identified and confirmed within the Michigan Birth Defects Registry from 1992 to 2005 (n = 406). Characteristics of infants with HLHS were compared with a 10:1 random control sample. Compared with 4060 control subjects, the 406 cases of HLHS were more frequently male (62.6% vs 51.4%), born prematurely (<37 weeks gestation; 15.3% vs 8.7%), and born at low birth weight (LBW) (<2.5 kg; 16.0% vs 6.6%). HLHS 1-year survival rate improved over the study period (P = .041). Chromosomal abnormalities, LBW, premature birth, and living in a high poverty neighborhood were significantly associated with death. Controlling for neighborhood poverty, term infants versus preterm with HLHS or LBW were 3.2 times (95% CI: 1.9-5.3; P < .001) more likely to survive at least 1 year. Controlling for age and weight, infants from low-poverty versus high-poverty areas were 1.8 times (95% CI: 1.1-2.8; P = .015) more likely to survive at least 1 year. Among infants with HLHS in Michigan, those who were premature, LBW, had chromosomal abnormalities, or lived in a high-poverty area were at increased risk for early death.